2021
DOI: 10.3390/agriculture11030240
|View full text |Cite
|
Sign up to set email alerts
|

The Deviation between Dairy Cow Metabolizable Energy Requirements and Pasture Supply on a Dairy Farm Using Proximal Hyperspectral Sensing

Abstract: This study aimed at determining the extent to which the deviation of daily total metabolizable energy (MEt) requirements of individual cows from the metabolizable energy (ME) supplied per cow (DME) varied throughout the production season in a pasture-based dairy farm using proximal hyperspectral sensing (PHS). Herd tests, milk production, herbage and feed allocation data were collected during the 2016–2017 and 2017–2018 production seasons at Dairy 1, Massey University, New Zealand. Herbage ME was determined fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Bhardwaj et al [ 61 ] reported the mean average DMY at early, mid, and late lactation stages were 2.0 ± 0.08 L, 2.99 ± 0.08 L, and 1.84 ± 0.09 L, respectively, which was dissimilar to the current study result. Furthermore, DMY at early, mid, and late lactation stages were 1.99 ± 0.08 L, 3.46 ± 0.10 L and 1.57 ± 0.084 L [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…Bhardwaj et al [ 61 ] reported the mean average DMY at early, mid, and late lactation stages were 2.0 ± 0.08 L, 2.99 ± 0.08 L, and 1.84 ± 0.09 L, respectively, which was dissimilar to the current study result. Furthermore, DMY at early, mid, and late lactation stages were 1.99 ± 0.08 L, 3.46 ± 0.10 L and 1.57 ± 0.084 L [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that the dry matter (DM) concentrations of alfalfa and corn silage in samples collected within farms exhibit large variability in both long-term and short-term periods [99]. In addition, the daily demand for the nutrition of individual lactating cows, such as metabolizable energy (ME), exhibited deviations due to the climate, diet, and animal factors [100]. Duranovich et al (2021) observed that the deviation of the estimated daily total metabolizable energy requirements of individual cows (MEt) from the actual ME supplied per cow in the herd varied greatly [100] (Table 3).…”
Section: Precision Nutritionmentioning
confidence: 99%
“…In addition, the daily demand for the nutrition of individual lactating cows, such as metabolizable energy (ME), exhibited deviations due to the climate, diet, and animal factors [100]. Duranovich et al (2021) observed that the deviation of the estimated daily total metabolizable energy requirements of individual cows (MEt) from the actual ME supplied per cow in the herd varied greatly [100] (Table 3). Moreover, many minerals have vital functions in mammals [101]; for example, phosphorus (P) has a role in energy metabolism, whereas copper (Cu) and zinc (Zn) are involved in immune functions [102].…”
Section: Precision Nutritionmentioning
confidence: 99%
“…UWP-PF is investigating the effects of alternative dairy production systems on water quality and nutrient cycling. Dairy 1 is evaluating breeds and crossbreeding for once-a-day milking ( Jiang et al, 2020 ) and the use of precision technology to feed cows more efficiently ( Duranovich et al, 2021 ). HAUF is mapping the impact (economic, environmental, and social indicators) of conversion from separate crop and livestock enterprises to a mixed circular crop-livestock farming system.…”
Section: Tailor Practices To Local Culture (Step 6)mentioning
confidence: 99%